“Pre-service English teachers’ experience in pre-professional practices” - Quintana Guamushig, Lizeth Stefania (2023)
This research study focuses on the perspective about the experiences of being a pre-professional practice student in a foreign language. The main objective is to describe pre-service English teachers´ experiences from the seventh and eighth semesters in pre-professional practices. This study is a qualitative approach that used a survey divided into two parts: strengths and challenges to get data. It was applied to twelve students from seventh and eighth “A”-“B” semesters at the Technical University of Cotopaxi. These populations were selected by “Purposive Sampling”. The results showed that the students had strengths and challenges in their pre-professional practice. The practitioners revealed strengths in methodology, (PPP) framework, technological resources, and self-confidence. In the same way, the pre-service English teachers showed their challenges in learning values, tutoring, curricular adaptation, and classroom management.